2015
DOI: 10.1517/14740338.2015.1105214
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in children: a ten-year review of reporting to the Portuguese Pharmacovigilance System

Abstract: Pediatric ADR represents about 10% of the reports received by the PPS. Most ADR were considered serious. Major findings varied according to age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
2
3
1
Order By: Relevance
“…Concerning the therapeutic substances involved in ADRs, our results confirm previously reported data ( Clavenna et al, 2009 ; Piovani et al, 2013 ; Nogueira Guerra et al, 2015 ; Ferrajolo et al, 2019 ). In fact, vaccines were the drug class involved in ADRs occurrence, especially in infants.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the therapeutic substances involved in ADRs, our results confirm previously reported data ( Clavenna et al, 2009 ; Piovani et al, 2013 ; Nogueira Guerra et al, 2015 ; Ferrajolo et al, 2019 ). In fact, vaccines were the drug class involved in ADRs occurrence, especially in infants.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are largely consistent with several previous studies investigating pediatric reporting patterns in other national and international SRSs [ 25 , 35 37 , 43 , 44 ]. In accordance with findings from VigiBase [ 37 ] and the Italian SRS database [ 25 ], most child ICSRs corresponded to children aged 2 up to 17 years and about 52% of all ICSRs concerned boys, mainly from 28 days to 17 years of age.…”
Section: Discussionsupporting
confidence: 93%
“…During the 10-year period covered by our analysis, after exclusion of duplicates, vaccines, and ICSRs containing missing age data, reporting of suspected ADRs in the pediatric population of the Calabria region represented about 6% of all ICSRs collected in the Calabrian Pharmacovigilance database. This proportion was lower than that reported in the EudraVigilance database (11.2%) [ 34 ] and the Portuguese pharmacovigilance database (9.7%) [ 35 ], but it was similar to the percentage of pediatric ICSRs reported in the whole RNF database (6.8%) [ 25 ], in the Spanish pharmacovigilance database (7%) [ 36 ], and in VigiBase (7.7%) [ 37 ]: similar to our study, the RNF database and VigiBase analyses excluded vaccine-related reports.…”
Section: Discussioncontrasting
confidence: 61%
“…In line with our results, data obtained from an analysis of AEFIs reported to the Danish Medicines Agency between 1998 and 2007 revealed that AEFIs most commonly referred to the following SOCs: “general disorders and administration site conditions,” “skin and subcutaneous tissue disorders,” and “nervous system disorders” ( Aagaard et al, 2011 ). Also the results of a further pharmacovigilance study showed that out of 1,742 reports (of which 42% referred to vaccine), ADRs/AEFIs most commonly referred to “general disorders and administration site conditions” and “skin and subcutaneous tissue disorders” ( Nogueira Guerra et al, 2015 ). An analysis of AEFIs’ reports from Switzerland in 2016 showed that, apart from the above mentioned SOCs, AEFIs were also related to SOCs “injury, poisoning, and procedural complications” and “musculoskeletal and connective tissue disorders” ( AEFI, 2018 ).…”
Section: Discussionmentioning
confidence: 99%